Structural equation modelling analysis of the relationship between transformational leadership style of coaches, sport commitment, and athletes' satisfiction among Iranian high school footbal players - Saybani, Hamidreza (2013)
The purpose of this study was to investigate the relationship between transformational leadership style of Iranian high schools‘ coaches and sport commitment and athletes‘ satisfaction of Iranian high schools‘ football players as well as the mediating role of athletes‘ satisfaction, and propose a coaching model. Descriptive statistics and correlations as well as inferential statistics were applied in this study. Structural equation modeling (SEM) and analysis of variance (ANOVA) were used to analyze the data, and to develop the model. This study was conducted in the Alborz province of Iran. The population of this study consists of 558 football players (15-20 years old). A total of 280 high schools‘ football players were selected from 31 high schools football teams using the simple random sampling procedure. Instruments used in this study were Multifactor Leadership Questionnaire (MLQ) (Avolio & Bass, 1995), Sport Commitment Model Scale (SCMS) (Scanlan et al.,1993), and Athlete Satisfaction Questionnaire (ASQ) (Riemer & Chelladurai, 1998). The results of the study indicated that there isa positive and significant relationship between transformational leadership style of coaches and sport commitment and athletic satisfaction of football players. The study showed that athlete satisfaction mediates the relationship between transformational leadership style and sport commitment. Mediation model illustrated that transformational leadership style would explain variance of sport commitment better than direct model. Therefore, it can be concluded that the transformational leadership style of coaches can increase sport commitment of football players through increasing athletes‘ satisfaction. In addition, the researcher found that there was no significant difference between age,football playing experience, and sport commitment of football players. Even though the results showed that a significant difference in athlete satisfaction between football players of different ages, the findings revealed that there was no significant difference in terms of athlete satisfaction between of football players of different football playing experience. Based on the results, it was concluded that the transformational leadership model is suitable for Iranian high schools‘ football coaches and it can improve the sport commitment of the football players by increasing their athletic satisfaction.